Drop-on-Demand Inkjet Printhead Performance Enhancement by Dynamic Lumped Element Modeling for Printable Electronics Fabrication. (23rd December 2014) - He, Maowei; Sun, Liling; Hu, Kunyuan; Zhu, Yunlong; Ma, Lianbo; Chen, Hanning
Abstract : The major challenge in printable electronics fabrication is the print resolution and accuracy. In this paper, the dynamic lumped element model (DLEM) is proposed to directly simulate an inkjet-printed nanosilver droplet formation process and used for predictively controlling jetting characteristics. The static lumped element model (LEM) previously developed by the authors is extended to dynamic model with time-varying equivalent circuits to characterize nonlinear behaviors of piezoelectric printhead. The model is then used to investigate how performance of the piezoelectric ceramic actuator influences jetting characteristics of nanosilver ink. Finally, the proposed DLEM is applied to predict the printing quality using nanosilver ink. Experimental results show that, compared to other analytic models, the proposed DLEM has a simpler structure with the sufficient simulation and prediction accuracy.